Utility of cardiovascular magnetic resonance in pregnancy - Aremu, Olukayode; Jermy, Stephen; Samuels, Petronella; Kahts, Morne; Muthithu, Daniel W.; Bana, Tasnim; Ntusi, Ntobeko A. B. (SA Heart Journal, 2022)
Pregnant women with known or suspected cardiovascular disease (CVD) often require cardiovascular imaging during pregnancy. Decisions about imaging in pregnancy are premised on understanding the physiology of pregnancy, understanding basic concepts of different imaging modalities, the clinical manifestations of existent CVD in pregnancy and features of new CVD. Cardiovascular magnetic resonance (CMR) imaging is safe in pregnancy and is not associated with any adverse foetal effects, provided there are no general contra-indications to magnetic resonance (MR) imaging. CMR also does not involve any ionising radiation. In pregnancy, CMR is useful to confirm diagnosis of CVD, assess disease severity, to stratify risk and prognosticate, to plan appropriate management, and to assess response to therapy. Use of any imaging test in pregnancy needs to have safety considerations balanced against the importance of accurate diagnosis and thorough assessment of the pathological condition. This review summarises the evolving role of CMR in evaluation of known or suspected new CVD in pregnancy.